2017
DOI: 10.1038/s41598-017-02267-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mismatch Negativity is Associated with Increased Plasma Level of Glutamate in First-episode Psychosis

Abstract: Reduced amplitude of mismatch negativity (MMN) is one of the more promising biological markers of schizophrenia. This finding holds true in both early and chronic phases of the disorder, and is compatible with the glutamatergic dysfunction hypothesis. To further establish MMN as a biomarker of aberrant glutamatergic neurotransmission, an exploration for an association with blood levels of glutamatergic amino acids is an important next step. Despite a large body of work investigating MMN in schizophrenia, no pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 61 publications
7
33
0
4
Order By: Relevance
“…Only asparagine level decreased after treatment, but it was still higher compared to control group. Our results supported the previous findings of increased plasma glutamate level in FEP patients (Nagai et al, ). Similarly, a proton magnetic spectroscopy study revealed that glutamate level was increased in the striatum and cerebellum in FEP patients before the treatment (De La Fuente‐Sandoval et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Only asparagine level decreased after treatment, but it was still higher compared to control group. Our results supported the previous findings of increased plasma glutamate level in FEP patients (Nagai et al, ). Similarly, a proton magnetic spectroscopy study revealed that glutamate level was increased in the striatum and cerebellum in FEP patients before the treatment (De La Fuente‐Sandoval et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…There are a few numbers of studies investigating blood serine levels in FEP patients compared to ones in schizophrenia patients. Nagai et al () did not show any difference for l ‐serine, d ‐serine, glycine, and glutamine in FEP patients compared to healthy subjects and ultra‐high risk individuals. However, we showed a significant increase in serine and glutamine levels in FEP patients.…”
Section: Discussionmentioning
confidence: 91%
“…The onset of the auditory MMN response occurs within 50 ms of the deviant stimulus, and peaks after an additional 100–150 ms . MMN is thought to reflect auditory sensory memory or pre‐attentive processing . P300 is a positive‐going wave in the event‐related potential and is elicited during oddball paradigm with a latency of roughly 250–300 ms after deviant stimulus.…”
Section: Evidence Supporting the Nmdar Hypothesismentioning
confidence: 99%
“…Moreover, some studies have provided more direct evidence, showing the linkage of these attenuations and glutamate hypothesis in schizophrenia. For example, the plasma levels of glutamatergic amino acids were correlated with MMN amplitude attenuation in subjects in the early stages of psychosis . Another EEG and MRS study suggested that there were positive correlations between P300 amplitude and both the glutamine/glutamate ratio and the glutamine concentration in the anterior cingulate .…”
Section: Evidence Supporting the Nmdar Hypothesismentioning
confidence: 99%
“…However, here, during adolescence the reduction in MMN is significant and much greater in those with schizophrenia than bipolar disorder at the outset. A shared pathology may still be indicated because reduced MMN is related to N-methyl-D-aspartate receptor (NMDAR) dysfunction in schizophrenia and in first episode psychosis, and is associated with higher plasma levels of glutamate (Nagai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%